Neocolonialism in Black Panther “Wakanda forever” Movie - Kusen, Felicia Jessica; Saputra, Felicia Celine; Tambunan, Aubrey Jemima; Silaen, Gwyneth Lillian; Patricia, Catherine (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2023)
This study aims to show Neocolonialism in the movie